Imitation in faith: enacting Paul’s ambiguous "pistis Christou" formulations on a Greco-Roman stage - Sierksma-Agteres, Suzan (International journal of philosophy and theology, 2016)
There is an ongoing debate in New Testament scholarship on the correct interpretation of Paul’s pistis Christou formulations: are we justified by our own faith/trust in Christ, or by participating in Christ’s faith and faithfulness towards God? This article contributes to the position of purposeful or sustained ambiguity by reading Paul’s imitation - and faith(fulness) - language against the background of Hellenistic-Roman thought on and practice of imitation. In particular, the mimetic chain between teachers and students training for a philosophical disposition, and the philosophical topos of "becoming like God"(homoiōsis theōi) offer material valuable for comparison. Since pistis, fides and cognates are used in these settings as both a quality to imitate and as attitude towards a model, and since, conversely, imitation is very much involved in Paul’s pistis-vocabulary, it makes sense to read pistis Christou as shorthand for a mimetic movement of faith(fulness) via Christ towards God.